Vulnerable pregnant women in antenatal practice: Caregiver's perception of workload, associated burden and agreement with objective caseload, and the influence of a structured organisation of antenatal risk management. (September 2016) - de Groot, Nynke; Venekamp, Angélica A.; Torij, Hanneke W.; Lambregtse-Van den Berg, Mijke P.; Bonsel, Gouke J.
Abstract: Introduction: pregnancy care for vulnerable women is often perceived as a burden by caregivers as vulnerable clients require complex case management, additional time, and more often show adverse perinatal outcomes. Vulnerable clients bring about additional work strain for the caregiver, especially when the workload is high. We define client vulnerability as coexistence of psychopathology, psychosocial problems or substance use, together with features of deprivation. We investigated, as part of a national programme, whether the subjective caregiver's perception of workload and the objective registry-based caseload of vulnerable clients are in agreement, and whether a structured organisation of antenatal risk management reduces the burden associated with the perceived workload, in particular if the objective caseload is high. Methods: we combined three data sources: (1) at the unit level (i.e. midwifery practice, obstetric unit) interview data from caregivers, from which we derived a) the (subjective) caregiver's perception of workload, b) the associated burden and c) organisational structure of antenatal risk management, (2) at the unit level perinatal registry data, from which we derived a) unit characteristics and b) (objective) unit specific caseload, and (3) at the individual client level survey data collected during the first antenatal visit, from which the prevalence of vulnerable clients was derived. The study area was the South-West Netherlands (2.5 million inhabitants), containing areas with varying degrees of urbanisation and deprivation. Findings: sixteen units had complete data on all measures. Generally, subjective workload and objective caseload were only weakly related, the relation being modified by the organisation of antenatal risk management. If the organisational structure of antenatal risk management was low, the experienced burden was high, even if the objective caseload was low. Highly structured antenatal risk management was associated with a medium to low burden. Discussion: our observational study suggests that even a high caseload can be dealt with by structured antenatal risk management. A change from the current individual case-finding policies towards a more universal screen-like approach may thus benefit both the client and the caregiver. Highlights: Vulnerable clients are a challenge in antenatal care; in deprived areas they induce a high work strain on care professionals. In a large Dutch region, professionals jointly selected improvement of care to vulnerable clients as research and care priority. Objective vulnerability caseload was generally higher than estimated workload by unit professionals. A high degree of structure of antenatal risk management was associated with a lower subjective burden. Care for vulnerable women might benefit from a screening-like approach.